LQR design with prescribed damping and degree of stability - Misra, P. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
This note addresses the problem of linear quadratic regulator design such that the eigenvalue of the closed loop state matrix lie to the left of a desired constant (-/spl alpha/) and satisfy certain minimum damping to achieve a desirable response. A computational algorithm is outlined and simulation results are provided.